Stable, multigenerational transmission of the bean seed microbiome despite abiotic stress - Sulesky-Grieb, Abby; Simonin, Marie; Bintarti, A. Fina; Marolleau, Brice; Barret, Matthieu; Shade, Ashley (mSystems, 2024)
Seed microbiomes initiate plant microbiome assembly and thus have critical implications for the healthy development and performance of crops. However, the consequences of environmental conditions of the parent plant for seed microbiome assembly and transmission are unknown, but this is critical information, given the intensifying stressors that crops face as the climate crisis accelerates. This study provides insights into the maintenance of plant microbiomes across generations, with implications for durable plant microbiome maintenance in agriculture on the changing planet.